Beyond Translation: Music, Language, and Mediation - Antón Moreno, Miguel (Revista de Filosofía, 2026)
This article reconsiders the problem of musical meaning by reformulating the relationship between music and language. Through a critical reading of Friedrich Nietzsche and Claude Lévi-Strauss, it examines two insufficient interpretive models: the illustrative model, which subordinates music to prior conceptual contents, and the naturalist model, which seeks to ground its intelligibility in physiological determinations. Against both approaches, musical meaning is understood as a form of non-propositional, non-univocal, and non-arbitrary openness, articulated through operations of cultural ordering and partially stabilized by interpretive mediations. From this perspective, mimesis is redefined as a principle for configuring the sonic continuum, while musical autonomy is conceived as resistance to full translation, rather than as isolation from language or culture.